Correction to: A Standards Organization for Open and FAIR Neuroscience: the International Neuroinformatics Coordinating Facility (Neuroinformatics, (2021), 10.1007/s12021-020-09509-0) - Abrams, M.B. (Springer, 2021)
The original version of this article unfortunately contained mistakes. (1) These authors were assigned with incorrect affiliation/s: Trygve B. Leergaard, Helen S. Mayberg, Luciano Milanesi, Roman Moucek, J. B. Poline, Prasun K. Roy, Stephen C. Strother, Tong Boon Tang, Paul Tiesinga, Thomas Wachtler, Daniel K. WÃ³jcik, and Maryann E. Martone. (2) Serendipitea.Eorld, Hasselby, Sweden should be Serendipitea.World, Hasselby, Sweden. The original article has been corrected. Â© 2021, The Author(s).